Pelatihan Pengendalian Risiko pada Keselamatan Kerja di Jasa Binatu - Dian Mardi Safitri; Nora Azmi; Ika Wahyu Utami; Larasati Rizky Putri; Harum Yuniarti; Azizah Nurul Hanifati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2023)
Laundry services are essential to support other industries, such as tourism and health. Hospitals, hotels, and restaurants are customers of the laundry industry. Occupational health and safety risks in the laundry sector have become a government concern through the Ministry of Health of the Republic of Indonesia issuing the Hospital Laundry Ergonomics Guide. This activity aims to provide knowledge regarding occupational safety risk control for the laundry service industry. Workers in this sector face risks of ergonomics and chemical hazards. Ergonomics risk comes from lifting and transporting linen material in sorting, washing, and drying activities up to the final process. Workers need to be given the insight to care about safety and how to control the hazards they face. By carrying out this activity, it is hoped that participants will become more aware of occupational safety risk control to improve their quality of life.